Evidence for Elizabethkingia anophelis Transmission from Mother to Infant, Hong Kong - Susanna K.P. Lau; Alan K.L. Wu; Jade L.L. Teng; Herman Tse; Shirly O.T. Curreem; Stephen K.W. Tsui; Yi Huang; Jonathan H.K. Chen; Rodney A. Lee; Patrick C.Y. Woo; Kwok-Yung Yuen (Emerging Infectious Diseases, 2015)
Elizabethkingia anophelis, recently discovered from mosquito gut, is an emerging bacterium associated with neonatal meningitis and nosocomial outbreaks. However, its transmission route remains unknown. We use rapid genome sequencing to investigate 3 cases of E. anophelis sepsis involving 2 neonates who had meningitis and 1 neonate’s mother who had chorioamnionitis. Comparative genomics revealed evidence for perinatal vertical transmission from a mother to her neonate; the 2 isolates from these patients, HKU37 and HKU38, shared essentially identical genome sequences. In contrast, the strain from another neonate (HKU36) was genetically divergent, showing only 78.6% genome sequence identity to HKU37 and HKU38, thus excluding a clonal outbreak. Comparison to genomes from mosquito strains revealed potential metabolic adaptations in E. anophelis under different environments. Maternal infection, not mosquitoes, is most likely the source of neonatal E. anophelis infections. Our findings highlight the power of genome sequencing in gaining rapid insights on transmission and pathogenesis of emerging pathogens.